2007
DOI: 10.1073/pnas.0610045104
|View full text |Cite
|
Sign up to set email alerts
|

Altered soil microbial community at elevated CO 2 leads to loss of soil carbon

Abstract: Increased carbon storage in ecosystems due to elevated CO2 may help stabilize atmospheric CO 2 concentrations and slow global warming. Many field studies have found that elevated CO 2 leads to higher carbon assimilation by plants, and others suggest that this can lead to higher carbon storage in soils, the largest and most stable terrestrial carbon pool. Here we show that 6 years of experimental CO 2 doubling reduced soil carbon in a scrub-oak ecosystem despite higher plant growth, offsetting Ϸ52% of the addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
343
4
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 456 publications
(376 citation statements)
references
References 30 publications
24
343
4
5
Order By: Relevance
“…According to this theory, the soil C-specialists increase in abundance by utilizing some of the new labile C and persist to degrade stable soil C when the labile C becomes diminished (Fontaine et al 2003). Supporting evidence for this mechanism is provided by studies that measured prolonged priming after supply of added labile C is exhausted (Fontaine et al 2004), and priming alongside an increased dominance of the microbial community by fungi (Carney et al 2007).…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…According to this theory, the soil C-specialists increase in abundance by utilizing some of the new labile C and persist to degrade stable soil C when the labile C becomes diminished (Fontaine et al 2003). Supporting evidence for this mechanism is provided by studies that measured prolonged priming after supply of added labile C is exhausted (Fontaine et al 2004), and priming alongside an increased dominance of the microbial community by fungi (Carney et al 2007).…”
Section: Introductionmentioning
confidence: 62%
“…Priming has been suggested as the cause of reductions in soil C in temperate forest grown under experimentally elevated CO 2 , despite increased inputs of plant-C to soils (Carney et al 2007;Langley et al 2009). The parallel loss of soil C and increase in N mineralization in the study by Langley et al (2009) suggests that priming occurred due to microbial 'co-metabolism' of organic matter to acquire N (Kuzyakov et al 2000), which is often considered the limiting nutrient in temperate forests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…going from a high fertility agricultural soil to a forest soil with a declining soil fertility status Hoosbeek and Scarascia-Mugnozza, 2009). In a scrub-oak ecosystem with higher biomass production under elevated [CO 2 ], Carney et al (2007) observed a decline of soil C due to relative higher abundances of fungi and higher activities of phenol oxidase which is responsible for the degradation of recalcitrant SOM such as lignin. Based on incubation experiments at the Duke FACE experiment, Billings and Ziegler (2008) inferred that increasing N limitation under elevated [CO 2 ] would result in greater turnover rates of relatively stable soil C pools.…”
Section: Soil N and N Uptakementioning
confidence: 99%
“…To date, the majority of studies on ecosystem C storage response triggered by climate change have been focused on the role of above-ground tissue chemistry and biomass production 12 , the dynamics of total terrestrial C capacity 13 , and more recently in identifying microbial indices of C utilization and activity that lead to trace gas production [14][15][16][17] . However, little is known about the degree to which soil microbialderived C persists in the soil, and contributes to stable C. Microbial production of recalcitrant organic C lies at the root of two issues of global concern-maintaining soil productivity and controlling greenhouse gas levels 7 .…”
mentioning
confidence: 99%